Differential expression of cholangiocyte and ileal bile acid transporters following bile acid supplementation and depletion - Kip, N. Sertac (World J Gastroenterol, 2004)
AIM: We have previously demonstrated that cholangiocytes, the epithelial cells lining intrahepatic bile ducts, encode two functional bile acid transporters via alternative splicing of a single gene to facilitate bile acid vectorial transport. Cholangiocytes possess ASBT, an apical sodium-dependent bile acid transporter to take up bile acids, and t-ASBT, a basolateral alternatively spliced and truncated form of ASBT to efflux bile acids. Though hepatocyte and ileal bile acid transporters are in part regulated by the flux of bile acids, the effect of alterations in bile acid flux on the expression of t-ASBT in terminal ileocytes remains unclear. Thus, we tested the hypothesis that expression of ASBT and t-ASBT in cholangiocytes and ileocytes was regulated by bile acid flux. METHODS: Expression of ASBT and t-ASBT message and protein in cholangiocytes and ileocytes isolated from pair-fed rats given control (C) and 1% taurocholate (TCA) or 5% cholestyramine (CY) enriched diets, were assessed by both quantitative RNase protection assays and quantitative immunoblotting. The data obtained from each of the control groups were pooled to reflect the changes observed following TCA and CY treatments with respect to the control diets. Cholangiocyte taurocholate uptake was determined using a novel microperfusion technique on intrahepatic bile duct units (IBDUs) derived from C, TCA and CY fed rats. RESULTS: In cholangiocytes, both ASBT and t-ASBT message RNA and protein were significantly decreased in response to TCA feeding compared to C diet. In contrast, message and protein of both bile acid transporters significantly increased following CY feeding compared to C diet. In the ileum, TCA feeding significantly up-regulated both ASBT and t-ASBT message and protein compared to C diet, while CY feeding significantly down-regulated message and protein of both bile acid transporters compared to C diet. As anticipated from alterations in cholangiocyte ASBT expression, the uptake of taurocholate in microperfused IBDUs derived from rats on TCA diet decreased 2.7-fold, whereas it increased 1.7-fold in those on CY diet compared to C diet fed groups. CONCLUSION: These data demonstrate that expression of ASBT and t-ASBT in cholangiocytes is regulated by a negative feedback loop while the expression of these transporters in terminal ileum is modified via positive feedback. Thus, while transcriptional regulatory mechanisms in response to alterations in bile acid pool size are operative in both cholangiocytes and ileocytes, each cell type responds differently to bile acid supplementation and depletion.